2011
DOI: 10.1007/s12206-011-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy flow analysis of penetration beam-plate coupled structures

Abstract: This study concerns the transmission of vibrational energy through beam-plate junctions by energy flow analysis, which is an analytic tool for predicting the frequency averaged vibration response of built-up structures in the medium to high frequency ranges. A semiinfinite beam perpendicularly connected to an infinite plate is studied using the wave transmission approach. To calculate the power transmission and the reflection coefficients of the beam-plate junction, compatibility and equilibrium conditions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…k x , k y , and k z are the x, y, and z components of the complex wavenumber, k L , respectively. Substituting equation (13) into equation 4, the dispersion relation of the dilatational wave can be expressed as…”
Section: Derivation Of the Energy Governing Equations For A Dilatatiomentioning
confidence: 99%
See 1 more Smart Citation
“…k x , k y , and k z are the x, y, and z components of the complex wavenumber, k L , respectively. Substituting equation (13) into equation 4, the dispersion relation of the dilatational wave can be expressed as…”
Section: Derivation Of the Energy Governing Equations For A Dilatatiomentioning
confidence: 99%
“…Substituting equation (13) into equations (10)-(12), the expanded expressions of each components of the time-averaged intensity are derived as ð20Þ ð21Þ…”
Section: Derivation Of the Energy Governing Equations For A Dilatatiomentioning
confidence: 99%
“…However, in the frequency range for structure-borne sound studies is up to 8000Hz and the number of elements required is quite large to achieve satisfactory performance. The energy-based method such as statistical energy analysis (SEA) [2][3] for structureborne sound transmission at high frequencies can be used. However, Craik et al [4] reported that it was difficult to describe the coupling between the structure and cavity, making sound transmission loss calculation unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…Park and Hong 13 also derived energy governing equations for far-field propagating out-of-plane waves in the Mindlin plate. Song et al 14 extended this method to penetration beam-plate structures, in which a beam and a plate are coupled by a point junction. In addition, Kwon et al 15 developed energy flow models for out-of-plane waves in a finite thin shell, while Han et al 16 developed advanced energy flow models for Rayleigh–Love rods considering the effect of lateral inertia and Rayleigh–Bishop rods considering the effect not only of lateral inertia but also of shear stiffness.…”
Section: Introductionmentioning
confidence: 99%